Environmental life cycle assessment of railway bridge materials using UHPFRC - Fifer Bizjak, Karmen (RMZ-materials and geoenvironment, 2016)
The railway infrastructure is a very important component of the world%s total transportation network. Investment in its construction and maintenance is significant on a global scale. Previously published life cycle assessment (LCA) studies performed on road and rail systems very seldom included infrastructures in detail, mainly choosing to focus on vehicle manufacturing and fuel consumption. This article presents results from an environmental study for railway steel bridge materials for the demonstration case of the Buna Bridge in Croatia. The goal of these analyses was to compare two different types of remediation works for railway bridges with different materials and construction types. In the first part, the environmental impact of the classical concrete bridge construction was calculated, whereas in the second one, an alternative new solution, namely, the strengthening of the old steel bridge with ultra-high-performance fibre-reinforced concrete (UHPFRC) deck, was studied. The results of the LCA show that the new solution with UHPFRC deck gives much better environmental performance. Up to now, results of LCA of railway open lines, railway bridges and tunnels have been published, but detailed analyses of the new solution with UHPFRC deck above the old bridge have not previously been performed.
Keywords: railway; železnica; materiali LCA; materials; ife cycle assessment; LCA; bridge; most; natural environment; okolje; environmental